Model Pemberdayaan Masyarakat Berbasis Inovasi Radikal dan Circular Economy: Studi Kasus Lentera Sukamoro di PTBA Kertapati - Ainuddin, Ilham; Yuliana, Yuliana; ‘alim, Sarirotul; Safitri, Retnovivi (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose –This study aims to develop a community empowerment model based on radical innovation and circular economy through a case study of the Lentera Sukamoro program implemented by PT Bukit Asam Dermaga Kertapati. Novelty – The research introduces a new approach by integrating the circular economy into socio-environmental reclamation programs. The novelty also lies in the use of radical innovation to transform vulnerable groups. The four-pillar model developed emphasizes digitalization, waste utilization, and community structure strengthening as the foundation for sustainable empowerment. Methodology – This research employs a qualitative approach with an exploratory case study method at the PTBA Dermaga Kertapati site. Data were collected through in-depth interviews, focus group discussions (FGDs), observations, and document analysis. Data analysis was conducted using the interactive model of Miles & Huberman, which includes data reduction, data display, and conclusion drawing. Validity was ensured through triangulation of methods and sources. Findings – The findings indicate that the Lentera Sukamoro program has successfully fostered social transformation through an innovative and sustainable approach grounded in circular economy principles. The program integrates education, waste utilization, and community economic empowerment simultaneously. Limitations and Implications – The study is limited in terms of geographical scope and timeframe. Nevertheless, it contributes theoretically to the literature on social innovation and offers practical implications for companies and policymakers in designing more strategic, adaptive, and sustainable CSR initiatives. This study makes a significant contribution to the development of a community empowerment model based on radical innovation and the circular economy.